2019
DOI: 10.1177/1759091419886212
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the Motor Unit of a Fast-Twitch Lower Limb Skeletal Muscle in Huntington’s Disease

Abstract: Huntington's disease (HD) is a disorder characterized by chronic involuntary movements, dementia, and psychiatric symptoms. It is caused by a mutation in the gene that encodes for huntingtin protein (HTT), leading to the formation of mutant proteins expressed in various tissues. Although brain pathology has become the hallmark for HD, recent studies suggest that damage of peripheral structures also contributes to HD progression. We previously identified severe alterations in the motor units that innervate cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…By decreasing the excessive exposure to glutamate, its excitotoxicity can be modulated (Doble, 1999), resulting in a reduction of the caspase-mediated apoptosis, hence preventing neuronal death. In a previous study, we showed that the BACHD spinal cord motoneurons are atrophic (Valadão et al, 2017(Valadão et al, , 2019 and, possibly, die after significant activation of caspase-3. Here, we confirmed caspase-3 activation and found that CTK 01512-2 was able to reduce the apoptosis of the spinal cord neurons.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…By decreasing the excessive exposure to glutamate, its excitotoxicity can be modulated (Doble, 1999), resulting in a reduction of the caspase-mediated apoptosis, hence preventing neuronal death. In a previous study, we showed that the BACHD spinal cord motoneurons are atrophic (Valadão et al, 2017(Valadão et al, , 2019 and, possibly, die after significant activation of caspase-3. Here, we confirmed caspase-3 activation and found that CTK 01512-2 was able to reduce the apoptosis of the spinal cord neurons.…”
Section: Discussionmentioning
confidence: 90%
“…The number of images and the total area investigated are given in the figure legend for each experiment. For muscle fibre analyses, the sternomastoideus (STM) and tibialis anterior (TA) skeletal muscles were removed and processed according to the protocol previously published (Valadão et al, 2017(Valadão et al, , 2019 (n = 5 animals per group, per treatment). We chose STM and TA because STM is innervated by motoneurons mostly from the cervical portion of the spinal cord and TA by motoneurons from the lumbar segment.…”
Section: Microscopic and Immunofluorescence Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…HD muscle atrophy can result from the degeneration of different components of the motor unit, including the myofiber and the innervating motor neuron. Alteration of cervical and lumbar motor neurons was observed in HD mice [53][54][55]. Nonetheless, abnormalities were also detected in HD patient-derived muscle cells cultured in vitro, suggesting that some of the pathological features observed in vivo are cell-autonomous [56].…”
Section: Muscle Pathology In Polyglutamine Disease Patientsmentioning
confidence: 99%
“…At the cellular level, aggregation of mHTT, the inclusion of poly-ubiquitinated proteins were found in myofibers and myonuclei in R6/2 mice [ 9 , 71 ]. The mHTT formation in skeletal muscle leads to defects, such as myofiber size reduction, type switching, and denervation [ 69 , 72 , 73 , 74 , 75 ]. In addition to changes in myofiber structure, transcriptional deregulation, and deteriorations in energy metabolism occur linked to impaired adenine nucleotide metabolism [ 76 ].…”
Section: Purines In Huntington’s Diseasementioning
confidence: 99%